2021
DOI: 10.3390/ijms22094803
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photobehavior of a New Dehydrobenzoannulene-Based HOF with Fluorine Atoms: From Solution to Single Crystals Observation

Abstract: Hydrogen-bonded organic frameworks (HOFs) are the focus of intense scientific research due their potential applications in science and technology. Here, we report on the synthesis, characterization, and photobehavior of a new HOF (T12F-1(124TCB)) based on a dehydrobenzoannulene derivative containing fluorine atoms (T12F-COOH). This HOF exhibits a 2D porous sheet, which is hexagonally networked via H-bonds between the carboxylic groups, and has an interlayers distance (4.3 Å) that is longer than that of a typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…11. They typically have π-conjugated cores with benzene 49 [93], 50 [94], and 67 [95], triphenylene 51 [96], 52 [97], and 53 [97], acetylene bridged macrocycles 54 [98], 55 [99], 56 [98,100], and 57 [98], bowl-shaped sumanene 58 [101], hexaazatriphenylene (HAT) 59 [102], 60 [103],…”
Section: Hexacarboxylic Acidsmentioning
confidence: 99%
“…Tectons with planar π-conjugated hydrocarbon cores (49, 51, 52, 53, 54, 55, 56, and 57) and those with a planar N-hetero π-conjugated core (63) formed homotypic hlx sheets, which were stacked in an inverted fashion through π-π, CH-π and CH-O interactions to give noninterpenetrated, layered HOFs with AB stacking, although optimization of the recrystallization conditions, such as the temperature and the combination of solvents, was needed. The resulting offset arrangements of the AB stacked layers, on the other hand, differed from each other depending on the core structures [98] and substituents at the ortho-positions relative to the carboxy groups [97,99]. Kobayashi In the crystal structure, the peripheral phenylene groups of 49 were almost perpendicular to the central benzene ring due to steric hindrance, which resulted in a longer interlayer distance of 5.6 Å for the HOF [93].…”
Section: Zju-hof-1mentioning
confidence: 99%
“…Within the framework of this direction, only 11 articles have been published [ 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 ], among which there is 1 review. In terms of its subject matter, this direction, to some extent, intersects with both Thematic Area 5 and Thematic Area 6, since ions and radicals are among the objects of Thematic Area 5, and the structure and reactivity of these compounds, obtained as a result of theoretical research (carried out, as a rule, by quantum–chemical methods), are among the objects of Thematic Area 6.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…By analogy, with the systematization of articles indicated in Thematic Area 5, here, it is also advisable to subdivide all publications presented in it into two groups, in the first of which there will be articles on organic compounds, in the second, articles on inorganic compounds. Following this differentiation, the first of these groups should include 7 articles, namely [ 227 , 228 , 229 , 230 , 231 , 232 , 234 ], and the second, 4 articles [ 224 , 225 , 226 , 233 ]. The most significant among them, in our opinion, is review [ 231 ], devoted to the physical chemistry of one of the most stable known radicals, 2,2-diphenyl-1-(2,4,6-trinitrophenyl)hydrazyl (also called diphenylpycrylhydrazil or DPPH), which was opened in 1992, and will make it exactly 100 years old, in 2022.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%